A Review on Molecular Pathways of Procyanidin C1 in Modulating Inflammation, Oxidative Stress, and Apoptosis in Senescent Cells: Review Article (Journal of Pharma Insights and Research, 2025)
The progressive accumulation of senescent cells is a primary factor for tissue dysfunction, organismal aging, and the onset of age-related pathologies. While the therapeutic ablation of these cells, termed senolysis, holds immense promise, the development of agents with high selectivity and minimal off-target toxicity remains a critical pharmacological challenge. This review focuses on Procyanidin C1 (PCC1), a naturally occurring polyphenolic trimer derived from grape seed extract, which has emerged as a potent senotherapeutic candidate with a unique, dose-dependent dual mechanism. We analyze the molecular underpinnings of PCC1’s activity, detailing its capacity to induce apoptosis specifically in senescent cells via the amplification of oxidative stress and the upregulation of Bcl-2 family pro-apoptotic factors, Puma and Noxa. Simultaneously, at lower concentrations, PCC1 acts as a senomorphic agent, remodeling the Senescence-Associated Secretory Phenotype (SASP) by intercepting Nuclear Factor-kappa B (NF-κB) signaling. This paper also presents the structural prerequisites for the compound for activity and its efficacy in diverse biological contexts, from enhancing chemotherapy outcomes to mitigating organ fibrosis, positing PCC1 as a versatile tool in the advancement of longevity medicine.